Evaluation of Wound Healing and Cytotoxic Activities of Anacardic Acid (13:0) Isolated from Pistacia vera Hull Extract - Parisa Sarkhail*; Ghazal Hashemi; Effat Souri (Iranian Society of Pharmacognosy, 2024)
Background and objectives: Pistacia vera fruit is a popular nut belonging to Anacardiaceae family. Traditionally, the hulls have been used as herbal remedies for treatment of oral and skin wounds,peptic ulcers and hemorrhoids. Methods: In this study, anacardic acid (13:0) was elucidated by EI-MS, FTIR, 1D-NMR and 2D-NMR data analysisfrom active fraction. Cytotoxic activity was assessed against normal NIH/3T3 cells, and several cancerous human cells, including human breast cancer (MCF-7), hepatocarcinoma (HepG-2) and gastric cancer (MKN-45) using MTT assay. The wound healing activity of this compound was evaluated using in vitro scratch-wound healing assay on NIH/3T3 cells. Results: Anacardic acid (13:0) was toxic at the concentrations tested against all cell lines (6.25-100 µg/mL). Theselectivity index showed no selective cytotoxicity (SI< 2); however, anacardic acid (13:0) revealed significant wound healing effects through the migration of NIH/3T3 cells at the concentrations of 1.25-5 µg/mL. Conclusion: These results suggested that anacardic acid (13:0) from P. verahull has cytotoxic activity on human cancer cell lines and can also be useful as a bioactive molecule in wounds treatment. However, more in vitro and in vivo studies need to be done to confirm the efficacy and cytotoxicity of anacardicacid (13:0).